LA CRISE DE SOUVERAINETE MONETAIRE DANS LES TERRITOIRES D’ARU ET DE MAHAGI : Rébellion ou Agression monétaire ? - Oseyatoko, Marcel; Christian, NALINGAME DIVOVA (IJRDO - Journal of Social Science and Humanities Research, 2018)
The government of the Democratic Republic of Congo has engaged for several years the process of the "dedollarisation" of its economy to give again with the Franc congolais all the attributes of a national currency.¶  The American dollar had appeared in the economy congolaise at the beginning of the Nineties when inflation reached 200% (HTTP:// www.¶  slateafrique.com, consulted April 3, 2013 with 19h25).¶From 1986 so far, the rate of deposits in currency exceeds 50% and the lowest rate is 53, 94% in 1984;¶  66,81% in 1985 and 75,86% in 1986.¶  With the end of the year 2012, the "green tickets" accounted for 89% of deposits and 95.2% of the appropriations, according to the central bank of Congo.¶  Since this hyperinflation, the majority of the transactions are made in American dollar "American dollar".¶  But, for the restitution of its traditional functions to the national currency, the dedollarisation could consider a series of measurements being based on monetary policies, of exchange and budgetary.¶  Those will be carried out so as to:¶  to maintain a level of low inflation, to eliminate volatility from the rate of exchange, and finally maitriser conditions with the emergence of a money market in national currency substitutable with the currencies.¶  One could say that here, the dedollarisation is supposed to induce positive transformations such as the birth or the opening of the banking structure.¶  The principal argument is due to an néo-intermediation, the latter can not only entrainer one injection of capital but also to lead to a greater confidence in the banking structure.¶  The economic agents are reticent to deposit their liquidities in a bank with a less credible currency.¶  In front of this prospect, the transformations would lean in the direction of a larger company of the banking environment, with trade banks of right congolais more open to foreign competition, more competitive and offering services at weaker cost.¶Indeed, by eliminating the exchange rate risk, the use of only one currency can reduce the costs of transactions since the banks will be able to be freed from the provisions and the obstacles which theirs will be imposed.¶  Moreover, it will be also easier to them to borrow or lend on the money market.¶  The process of the dollarisation requires patience and of perseverance.¶  It also requires that one can engage it in the order and with method, the process must be accompanied by a good communication campaign in particular stressing the importance of the use of the national currency, as a symbol of national sovereignty, measuring unit, instrument of payment and store of value.¶  Because, dédollariser:¶  it is thus to reduce and control the perverse effects while increasing the attractivity of the national currency.¶  The government of the R.D Congo must combine the efforts of dédollariser in general the economy congolaise and that of the North-East in particular and should not standardize or minimize this plague which corrodes the saving in the North-East of the R.D Congo which would be likely one day to cause the frontier land conflict.¶